Evidence for dry molten globule-like domains in the pH-induced equilibrium folding intermediate of a multidomain protein - Acharya, Nirbhik; Mishra, Prajna; Jha, Santosh Kumar (Journal of Physical Chemistry Letters, 2016)
The role of van der Waals (vdW) packing interactions compared to the hydrophobic effect in stabilizing the functional structure of proteins is poorly understood. Here we show, using fluorescence resonance energy transfer, dynamic fluorescence quenching, red-edge excitation shift, and near- and far-UV circular dichroism, that the pH-induced structural perturbation of a multidomain protein leads to the formation of a state in which two out of the three domains have characteristics of dry molten globules, that is, the domains are expanded compared to the native protein with disrupted packing interactions but have dry cores. We quantitatively estimate the energetic contribution of vdW interactions and show that they play an important role in the stability of the native state and cooperativity of its structural transition, in addition to the hydrophobic effect. Our results also indicate that during the pH-induced unfolding, side-chain unlocking and hydrophobic solvation occur in two distinct steps and not in concerted manner, as commonly believed